Novel insights in the pathomechanism of Brugada syndrome and fever-related type 1 ECG changes in a preclinical study using human-induced pluripotent stem cell-derived cardiomyocytes - Li, Yingrui; Dinkel, Hendrik; Pakalniškytė, Dalia; Busley, Alexandra Viktoria; Cyganek, Lukas; Zhong, Rujia; Zhang, Feng; Xu, Qiang; Maywald, Lasse; Aweimer, Assem; Huang, Mengying; Liao, Zhenxing; et al. (Clinical and translational medicine, 2023)
Background Brugada syndrome (BrS) is causing sudden cardiac death (SCD) mainly at young age. Studying the underlying mechanisms associated with BrS type I electrocardiogram (ECG) changes in the presence of fever and roles of autophagy for BrS remains lacking. Objectives We sought to study the pathogenic role of an SCN5A gene variant for BrS with fever-induced type 1 ECG phenotype. In addition, we studied the role of inflammation and autophagy in the pathomechanism of BrS. Methods Human-induced pluripotent stem cell (hiPSC) lines from a BrS patient harboring a pathogenic variant (c.3148G>A/p. Ala1050Thr) in SCN5A and two healthy donors (non-BrS) and a CRISPR/Cas9 site-corrected cell line (BrS-corr) were differentiated into cardiomyocytes (hiPSC-CMs) for the study. Results Reductions of Nav1.5 expression, peak sodium channel current (INa) and upstroke velocity (Vmax) of action potentials with an increase in arrhythmic events were detected in BrS compared to non-BrS and BrS-corr cells. Increasing the cell culture temperature from 37 to 40°C (fever-like state) exacerbated the phenotypic changes in BrS cells. The fever-effects were enhanced by protein kinase A (PKA) inhibitor but reversed by PKA activator. Lipopolysaccharides (LPS) but not increased temperature up to 40°C enhanced the autophagy level in BrS-hiPSC-CMs by increasing reactive oxidative species and inhibiting PI3K/AKT signalling, and hence exacerbated the phenotypic changes. LPS enhanced high temperature-related effect on peak INa shown in BrS hiPSC-CMs. Effects of LPS and high temperature were not detected in non-BrS cells. Conclusions The study demonstrated that the SCN5A variant (c.3148G>A/p.Ala1050Thr) caused loss-of-function of sodium channels and increased the channel sensitivity to high temperature and LPS challenge in hiPSC-CMs from a BrS cell line with this variant but not in two non-BrS hiPSC-CM lines. The results suggest that LPS may exacerbate BrS phenotype via enhancing autophagy, whereas fever may exacerbate BrS phenotype via inhibiting PKA-signalling in BrS cardiomyocytes with but probably not limited to this variant.
Gesehen am 08.05.2023